Eyespan reflects reproductive quality in wild stalk-eyed flies - Hashim, Rosli; Pomiankowski, A.; Cotton, S.; Small, J. (2010)
Handicap models of sexual selection propose that females use male sexual ornaments as a cue in mate choice because they reflect commodities that increase female fitness, either directly or indirectly. In contrast to studies on vertebrates, most investigations of ornaments in insects and other invertebrate taxa have been conducted under laboratory conditions. There is a pressing need to address questions relating to sexual signalling of quality in natural populations, as the arbitrary and uniform environments found in the laboratory fail to reflect the world under which animals have evolved. We investigated associations between male ornaments (exaggerated eyespan), attractiveness, and reproductive quality in a wild population of the sexually ornamented stalk-eyed fly, Teleopsis dalmanni. We also explored the relationship between eyespan and reproductive quality in females to evaluate the potential for sexually antagonistic selection on eyespan. We show that eyespan is a generic correlate of reproductive quality, acting as a reliable mirror of variation in reproductive fitness in both sexes. Our findings suggest that male ornaments signal commodities that are of interest to females in the natural environment in which they, and mate preferences for them, have evolved. In addition, the covariance between female eyespan and reproductive output suggests that the former may be a reliable cue of quality in its own right. Our data provide important insights into the evolutionary forces that shape the evolution of exaggerated eyespan in wild populations of this species.